Near-peer education: a novel teaching program - de Menezes, Sara (Int J Med Educ, 2016)
OBJECTIVES: This study aims to: 1) Evaluate whether a near-peer program improves perceived OSCE performance; 2) Identify factors motivating students to teach; 3) Evaluate role of near-peer teaching in medical education. METHODS: A near-peer OSCE teaching program was implemented at Monash University’s Peninsula Clinical School over the 2013 academic year. Forty 3rd-year and thirty final-year medical students were recruited as near-peer learners and educators, respectively. A post-program questionnaire was completed by learners prior to summative OSCEs (n=31), followed by post-OSCE focus groups (n=10). Near-peer teachers were interviewed at the program’s conclusion (n=10). Qualitative data was analysed for emerging themes to assess the perceived value of the program. RESULTS: Learners felt peer-led teaching was more relevant to assessment, at an appropriate level of difficulty and delivered in a less threatening environment than other methods of teaching. They valued consistent practice and felt confident approaching their summative OSCEs. Educators enjoyed the opportunity to develop their teaching skills, citing mutual benefit and gratitude to past peer-educators as strong motivators to teach others. CONCLUSIONS: Near-peer education, valued by near-peer learners and teachers alike, was a useful method to improve preparation and perceived performance in summative examinations. In particular, a novel year-long, student-run initiative was regarded as a valuable and feasible adjunct to faculty teaching.